Restless dead : encounters between the living and the dead in ancient Greece - Johnston, Sarah Iles, 1957- (Berkeley : University of California Press, 1999)
Ancient Greek ideas about the dead evolved in response to changing social and cultural conditions - most notably changes associated with the development of the polis, such as funerary legislation, and changes due to increased contacts with cultures of the ancient Near East. Johnston presents and interprets these changes, using them to build a complex picture of the way in which the society of the dead reflected that of the living, expressing and defusing its tensions, reiterating its values and eventually becoming a source of significant power for those who knew how to control it.
Elpenor and others: narrative descriptions of the dead -- To honor and avert: rituals addressed to the dead -- Magical solutions to deadly problems: the origin and roles of the Goēs -- The unavenged: dealing with those who die violently -- Childless mothers and blighted virgins: female ghosts an their victims -- Hecate and the dying maiden: how the mistress of ghosts earned her title -- Purging the Polis: Erinyes, Eumenides, and Semnai Theai.
Includes bibliographical references (pages 289-307) and index.
Print version record.
JSTOR
Keywords: Ghosts -- Greece -- History; Greece -- Religion; Grèce -- Religion; BODY, MIND & SPIRIT -- Supernatural; RELIGION -- Antiquities & Archaeology; Ghosts; Religion; Greece; Dodenrijk; Beeldvorming; Sociale aspecten; Riten; Griekse oudheid; History